Determination of the Flexural Damage Curvature Capacity of R/C Columns - Aydemir, Cem; Kircil, Murat Serdar; Hancioglu, Baykal; Zorbozan, Mustafa (TURKISH CHAMBER CIVIL ENGINEERS, 2011)
Determination of the Flexural Damage Curvature Capacity of R/C Columns Instead of force based design methods, performance based design methods have been widely used especially for resistance assessment of existing buildings. Performance based design methods produce more realistic results compared to force based design methods for predicting probable structural damage level for a given earthquake considering inelastic properties of materials. To implement performance-based earthquake engineering, it is necessary to relate deformation demands placed on structural components to specific levels of damage. Turkish Seismic Design Code define three different damage limit states and corresponding concrete and reinforcement steel strain limits representing probable damage occuring at critical sections of R/C structural members. These limits are Minimum Damage Limit; Safety Limit and Collapse Limit state. In this study, a procedure to obtain total limit curvature of R/C columns is explained and interaction of the flexural damage limit curvature with various design parameters especially axial load level- are investigated. An equation showing dimensionless damage limit curvature and dimensionless axial load level relationship is derived. The results obtained with the proposed equation are compared with those obtained with the moment-curvature analyses and found to be compatible with experimental results.
Keywords: Damage limit states; strain limits; moment-curvature; strain hardening; confined concrete; CONCRETE BRIDGE COLUMNS; Engineering